A Male Breast Cancer: Case Study at RSUD dr. Iskak Tulungagung in 2024 - Regina, Ken Raos; Rosdiana, Yusfita Efi (Keluwih: Jurnal Kesehatan dan Kedokteran, 2026)
This case study explores the clinical and molecular profile of male breast cancer (MBC) and underscores the diagnostic utility of immunohistochemistry. A 79-year-old man was diagnosed with grade III invasive carcinoma of no special type (NST) via histopathology and immunohistochemistry, showing ER+, PR+, HER2 3+, and Ki67 (30%) expression. The tumor was classified as Luminal B-like (HER2-positive). The findings highlight the relevance of molecular profiling in guiding treatment and prognosis in rare male breast cancer cases.